PENGETAHUAN DAN SIKAP IBU TERHADAP PERAWATAN PAYUDARA PADA IBU HAMIL - Nani Zulfikar; Yufdel (Poltekkes Kemenkes Medan, 2023)
Breast care during pregnancy is an important part that must be considered in preparation for breastfeeding. Breast care is very important so that complications do not occur when breastfeeding the baby later. The aim of this research is to identify mothers' knowledge and attitudes towards breast care in pregnant women. This type of research is analytical survey research with a cross sectional approach. The population in this study was all third trimester pregnant women in the Muliorejo Community Health Center Working Area, Sunggal District, Deli Serdang Regency, totaling 30 people, sampling using total sampling technique. The instrument used is a questionnaire to determine knowledge of the number of statements in 20 questions to determine attitudes using a Liket scale for the number of statements in 10 questions. The data analysis used was univariate (Frequency Distribution. The research results showed that there were 15 people (75%) pregnant women who had good knowledge about breast care and there were 14 people (60%) pregnant women who had a positive attitude about breast care. Conclusion: Knowledge and The attitudes of pregnant women regarding breast care are 75% and 60%. Suggestions: Health promotion at the Muliorejo Community Health Center, Deli Serdang Regency regarding Breast Care is further improved with the hope that pregnant women will carry out breast care at their respective homes so that their births run smoothly.